Development of ecosystem for effective supply chains in 3D printing industry - an ISM approach. Issue 1 (June 2021) - Singh, S; Agrawal, V
Abstract: 3D printing (3DP) is an important technology to manufacture the objects of intricate designs that are otherwise not possible for traditional manufacturing. This technology has witnessed growth in research papers in the last decade that shows the increasing interest of researchers and users in this technology. Many researchers have predicted and written about the unimaginable new supply chain configurations after the large-scale adoption of 3D printing. A supply chain is a lifeline for any business because it drives the business by satisfying customers' demands economically. This study was undertaken to explore the factors that are critical for developing a supply chain ecosystem for the 3DP industry. The study used the literature of the relevant research papers, conference articles, additive manufacturing business reports, and supply chain management (SCM)research papers & articles on 3D printing technology. This study highlights factors that are critical for the supply chain ecosystem for the 3DP industry. Interpretive Structural Modelling (ISM) methodology identified interactive association among those factors. Impact Matrix Cross-Reference Multiplication Applied to a Classification (MICMAC analysis) has classified those factors into four categories for better understanding and strategy making. The stakeholders in the 3D printing industry can draw insights from the output of this study. Researchers can do further research on these factors for the benefit of sustainable supply chains in the 3DP industry.